Production of Colored Pigments with Amorphous Arrays of Black and White Colloidal Particles1. Issue 28 (27th May 2013) - Takeoka, Yukikazu; Yoshioka, Shinya; Takano, Atsushi; Arai, Shigeo; Nueangnoraj, Khanin; Nishihara, Hirotomo; Teshima, Midori; Ohtsuka, Yumiko; Seki, Takahiro
<x xml:space="preserve">Abstract</x> Sprayed: Pigments with various angle‐independent colors were prepared by a spray method (see picture), which is a remarkably simple method using submicrometer‐sized silica particles and carbon black. The use of a polyelectrolyte that adheres to the particles can stabilize the structure of the colloidal amorphous arrays to create highly stressable, nonfading pigments.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>